Advances and Refinement in Hyaluronic Acid Facial Fillers. Issue 2 (August 2016) - Costa, Christopher R.; Kordestani, Reza; Small, Kevin H.; Rohrich, Rod J.
Abstract : Summary: Fillers temporarily augment deflated or ptotic facial compartments to restore a youthful appearance. Hyaluronic acids predominate the fillers market because of their focal volumization, duration of effect, low incidence of adverse reactions, and reversibility. Being able to properly perform these in-office procedures will ensure safety for patients and provide aesthetically optimal results. This communication provides the senior author's (R.J.R.) stepwise approach to facial aging and deflation with soft-tissue injectable fillers. Abstract : Supplemental Digital Content is available in the Text.